Oxynoemacheilus amanos, a new nemacheilid loach from the Orontes River drainage (Teleostei: Nemacheilidae) - Kaya, Cüneyt; Yoğurtçuoğlu, Baran; Freyhof, Jörg (Zootaxa, 2021)
Oxynoemacheilus amanos, new species, is described from İncesu spring in the upper Hupnik drainage, a northern tributary of the lower Orontes in Turkey. It is distinguished from the other Oxynoemacheilus species in the Eastern Mediterranean Sea basin by possession of an incomplete lateral line with 23–45 pores, terminating between the vertical through the dorsal fin origin and the anus, 10–13 pores in the infraorbital canal, a deeply emarginate caudal fin, no suborbital groove in the male, and a series of irregularly shaped and set dark-brown bars on the flank, not connected to saddles on the back.